Poetic tradition and the voice of the translator: The first verse translations of Dante’s Commedia (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2017)
This paper analyses and compares the variety of text types in the first verse translations of Dante’s Commedia: the Catalan translation by Andreu Febrer (1429), the Spanish translation by Pedro Fernández de Villegas (printed in 1515), and an anonymous French translation preserved in a manuscript dating from between 1491 and 1530. All these translations are the first verse translations of the work into their respective languages.